Moderate Islam in Indonesia: Activities of Islamic Da'wah Ahmad Syafii Maarif - Suhaimi Suhaimi; Raudhonah Raudhonah (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2020)
This study aims to observe the activities of the preaching of Ahmad Syafii Maarif as a manifestation of Islamic moderation in the frame of humanity and Indonesian-ness. Ahmad Syafii Maarif in his various ideas always presents a portrait of Islam in Indonesia that is inclusive and tolerant. Where the construction of Islamic da'wah is based on Islamic doctrine as a religion of enlightenment that rahmatan lil alamin. The research was conducted through a literature approach by examining various ideas of Ahmad Syafii Maarif. Data collection techniques are done through a discourse analysis and interview approach. The results of this study indicate that the figure of Buya Syafii Maarif runs moderate Islamic da'wah activities or persuasive Islamic da'wah by interpreting makruf as something known and accepted by reason and by the public. while evil is something that is rejected by common sense. Syafii Maarif's moderate da'wah activities were conceptualized into three main Islamic ideas, namely Islam, humanity, and Indonesian-ness. Ahmad Syafii Maarif consistently carried out persuasive and rational Islamic da'wah, not intimidation propaganda. Besides, the existence of the Maarif Institute aims to smooth activities to voice his thoughts about the teachings of Islam so that the character and characteristics of moderate Indonesian Islam are socialized.Penelitian ini bertujuan meneropong aktivitas dakwah Ahmad Syafii Maarif sebagai manifestasi moderasi Islam dalam bingkai kemanusiaan dan keindonesiaan. Ahmad Syafii Maarif dalam berbagai gagasannya selalu menampilkan potret Islam di Indonesia yang inklusif dan toleran. Dimana konstrusi dakwah Islam didasarkan pada doktrin Islam sebagai agama pencerahan yang rahmatan lil alamin. Penelitian dilakukan melalui pendekatan kepustakaan dengan mengkaji berbagai gagasan Ahmad Syafii Maarif. Teknik pengumpulan data dilakukan melalui pendekatan analisis wacana dan wawancara. Hasil penelitian ini menunjukkan sosok Buya Syafii Maarif menjalankan aktivitas dakwah Islam moderat atau dakwah Islam persuasif dengan memaknai makruf sebagai sesuatu yang dikenal dan diterima oleh akal maupun oleh masyarakat. sedangkan munkar adalah sesuatu yang ditolak oleh akal sehat. Aktivitas dakwah moderat Syafii Maarif dikonsepsikan ke dalam tiga gagasan keislaman utama, yakni keislaman, kemanusiaan dan keindonesiaan. Ahmad Syafii Maarif konsisten melakukan dakwah Islam persuasif dan rasional, bukan dakwah intimidatif. Selain itu, keberadaan Maarif Institute bertujuan untuk kelancaran kegiatan menyuarakan pemikirannya tentang ajaran Islam sehingga tersosialisasikannya watak dan ciri khas Islam Indonesia yang moderat.